Development of an application of a pipeline network calculation - Kharitonova, O S; Volodchenko, T V; Bronskaya, V V; Ignashina, T V; Balzamov, D S; Khairullina, L E; Minnegalieva, Ch B (Journal of physics. Conference series, 2020)
The main stages of development of a pipe network calculation application at the coding level in C# language are presented. Databases are implemented by Microsoft SQL Server. Visual Studio was used as an integrated development environment for code writing, as well as a rich set of control elements written using .NET Framework. The necessary solutions for the task was developed after complementing the functionality of these code control elements.